Proceedings of the 2021 Conference of the North American Chapter of the Association for Computational Linguistics: Human Langua 2021
DOI: 10.18653/v1/2021.naacl-main.347
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Medical Self-Disclosure in Online Communities

Abstract: Self-disclosure in online health conversations may offer a host of benefits, including earlier detection and treatment of medical issues that may have otherwise gone unaddressed. However, research analyzing medical selfdisclosure in online communities is limited. We address this shortcoming by introducing a new dataset of health-related posts collected from online social platforms, categorized into three groups (NO SELF-DISCLOSURE, POSSI-BLE SELF-DISCLOSURE, and CLEAR SELF-DISCLOSURE) with high inter-annotator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Previous research found that high self-disclosure social media posts receive fewer upvotes, but more comments and a higher response rate (Balani and De Choudhury 2015;Valizadeh et al 2021). Researchers observed a negative association between self-disclosure and network size on Twitter (Wang, Burke, and Kraut 2016).…”
Section: Related Workmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous research found that high self-disclosure social media posts receive fewer upvotes, but more comments and a higher response rate (Balani and De Choudhury 2015;Valizadeh et al 2021). Researchers observed a negative association between self-disclosure and network size on Twitter (Wang, Burke, and Kraut 2016).…”
Section: Related Workmentioning
confidence: 97%
“…We labeled these reviews based on broad categories derived from different types of self-disclosure described in prior work. These categories consisted mostly of self disclosure in areas other than e-commerce, such as search (Weber and Jaimes 2011;Bi et al 2013), online profiles (in e-commerce and social media) (Ma, Hancock, and Naaman 2016;Ma et al 2017), social media platforms (Bak, Kim, and Oh 2012;Wang, Burke, and Kraut 2016;Zhao et al 2016;Walton and Rice 2013;Saha et al 2021;Zhao et al 2014Zhao et al , 2016 and online communities (Kou and Gray 2018;Valizadeh et al 2021;Balani and De Choudhury 2015;Yang, Yao, and Kraut 2017;Barak and Gluck-Ofri 2007;Yang, Yao, and Kraut 2017).…”
Section: A Taxonomy Of Self-descriptionmentioning
confidence: 99%
“…• detection of events [29,30], including self-harm events [31]; • extraction of diagnoses [13,[32][33][34][35] and their codes [36][37][38]; • recognition of named entities [5,14,[39][40][41], and more specifically of personal information [21,42,43] and family history [20]; • localization of advices [44] and arguments [45] in scientific literature; • extraction of relations [46][47][48], including temporal [49] and causality [50,51] relations.…”
Section: Information Extractionmentioning
confidence: 99%
“…Predicting depression on social media is a long standing research track (De Choudhury et al, 2021), and social media has also shown that signals to identify suicidal ideation can be traced with high efficacy (Choudhury et al, 2016). Platforms like Reddit 4 can be instrumental in terms of support, resources, and self-disclosure about mental health (Choudhury and De, 2014;Valizadeh et al, 2021). One of the first traceable thematic identifications of correlated, quantifiable information regarding mental state and wellbeing was by Fleming et al (1992), suggesting that a lack of social support combined with social isolation was present in patients showing signs of depression or post-partum depression.…”
Section: Feature Correlation Across Varying Mental Health Conditionsmentioning
confidence: 99%